Information security and storage of Internet of Things based on block chains - Liu, YiHe; Zhang, Shuang (Future generation computer systems, 2020)
With progress in science and technology and the rapid development of the Internet of Things, we have entered the intelligent era of the Internet of Things. With many devices connected to the Internet, hackers have opportunities to attack; thus, the security of the Internet of Things has attracted increased attention. In the era of big data, the demand for information storage is increasing. This paper considers block chains and proposes an ECC (Ellipse Curve Cryptography) asymmetric algorithm to encrypt information. For storage, this paper proposes compressed sensing for data compression reconstruction to improve information storage speed in the Internet of Things. The experimental results show that the proposed algorithm is superior to comparable algorithms in security and storage performance. •This paper completes data compression reconstruction based on block chain, thus speeding up data storage.•The experimental results also verify the effectiveness of this method.